Drug Inventory Management Using ABC-VEN and EOQ Analysis for Improving Hospital Efficiency - Soraya, Clara; Surwanti, Arni; Pribadi, Firman (Universitas Aisyah Pringsewu, 2022)
Pharmaceutical Installation at Hospital is a service unit that has a very large influence on hospital services and income from hospitals because the source of income and expenses comes from pharmaceutical installation activities in procurement to distribution. This research is a study on inventory management for Pharmaceutical supplies at Santo Yusup Boro Kulon Progo Hospital, Yogyakarta, this study aims to find a suitable inventory management calculation method that can be applied in hospitals, researchers chose ABC-VEN analysis to be applied to hospital pharmacy supply planning, as well as calculating the optimum number of orders in pharmaceutical drug supply, using EOQ calculations (Economic Order Quantity), as well as calculating when the reorder time (ROP) for the type of supply in pharmacy. This research method is a type of analytical descriptive research, the subjects of this study are the head of the service, head of finance, Head of Pharmacy installation, Head of Pharmacy and Hospital Therapy Team, other TFT members, as well as secondary data in the form of pharmaceutical sales reports, pharmacy reports in the form of opnam stock reports, reports of expired drugs, etc., data processing based on analytical descriptive using Microsoft excel. Where the results of the study from the number of pharmaceutical supplies at Santo Yusup Boro Hospital were 465 Drug items after being classified based on ABC-VEN analysis, 18 drugs entered the AV group, 20 drugs in the BV group, and 57 drugs including the CV group, after grouping based on ABC-VEN analysis in calculating the Optimum value of ordering drugs respectively, drug items, after using calculations based on ABC-VEN and EOQ analysis there was the efficiency of Rp. 22,206,511.52 in one year or there was efficiency of 41.8%. The conclusion of this study shows that the ABC VEN and EOQ methods can increase efficiency in the supply of medicines in hospital pharmacy installations, so this method is suitable for application in hospitals to manage supplies in hospitals.Abstrak: Instalasi Farmasi di Rumah sakit merupakan, unit pelayanan yang memiliki pengaruh sangat besar terhadap pelayanan rumahsakit serta pendapatan dari rumahsakit, karena sumber pendapatan maupun pengeluaran bayak bersumber dari aktivitas instalasi farmasi dalam pengadaan sampai dengan pendistribusian.Penelitian ini merupakan penelitian tentang inventory manajemen untuk perbekalan Farmasi di RSU Santo Yusup Boro Kulon Progo, Yogyakarta, penelitian ini bertujuan untuk mencari suatu metode perhitungan inventory manajemen yang cocok yang dapat diterapkan di RS, peneliti memilih analisi ABC-VEN untuk dapat di terapkan pada perencanaan persedian farmasi RS, serta menghitung jumlah pemesanan Optimum pada persedian obat farmasi, dengan memakai perhitungan EOQ( Economik Order Quantiti ), serta menghitung kapan waktu pemesanan kembali (ROP) untuk jenis persedian yang ada di farmasi. Metode penelitian ini merupakan jeneis penelitian deskriptik analitik, subyek penelitian ini adalah kepala bidang pelayanan, kepala bidang keuangan, Kepala instalasi Farmasi, Ketua Tim Farmasi dan Terapi RS, anggota TFT lainya, serta data sekunder berupa laporan penjualan farmasi, laporan farmasi berupa laporan stok opnam, laporn obat kadaluarsa dsb, pengolahan data berdasarka deskriptik analitik mengunakan Microsof exel. Dimana hasil penelitian dari jumlah persedian farmasi RSU Santo Yusup Boro sebanyak, 465 Item obat setelah di golongkan berdasarkan analisi ABC-VEN terdapat 18 obat yang masuk golongan AV, 20 obat masuk golongan BV, serta 57 obat termasuk kelompok CV, setelah dilakukan pengelompokan berdasarkan analisi ABC-VEN di hitung nilai Optimum pemesanan obat masing- masing, item obat, setelah mengunakan perhitungan bedasarkan analisi ABC-VEN dan EOQ terjadi Efisiensi sebesar Rp 22.206.511,52 dalam satu tahun atau terjadi efisiensi sebesar 41,8 %. Konklusi dari penelitian ini menunjukan bahwa metode ABC VEN dan EOQ mampu meningkatkan efisiensi pada persediaan obat-obatan di instalasi farmasi rumah sakit, sehingga metoda ini cocok untuk diaplikasikan di rumah sakit untuk mengelola persediaan di rumah sakit.